Estimation of frequency and amplitude of ring oscillator built using current sources - Abir J. Mondal; J. Talukdar; Bidyut K. Bhattacharyya (Ain Shams Engineering Journal, 2020)
In this paper a method is proposed to derive an equation for the oscillation frequency and amplitude of a ring oscillator built using two different current sources. Taking into consideration the transistor’s region of operation, the proposed method estimates the variation in oscillation frequency because of externally added load capacitance, supply voltage and number of stages. The analytical model so proposed is justified using 0.18 μm and 0.09 μm CMOS technology for a 5 stages ring oscillator. Indeed, the estimated oscillation frequency agrees with the simulated one, while the error was within 5%.